2019
DOI: 10.1007/s11128-019-2483-3
|View full text |Cite
|
Sign up to set email alerts
|

An infinite family of circulant graphs with perfect state transfer in discrete quantum walks

Abstract: We study perfect state transfer in Kendon's model of discrete quantum walks. In particular, we give a characterization of perfect state transfer purely in terms of the graph spectra, and construct an infinite family of 4-regular circulant graphs that admit perfect state transfer. Prior to our work, the only known infinite families of examples were variants of cycles and diamond chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The phenomenon of perfect state transfer (PST) in quantum communication networks was originally introduced by Bose in [14]. This work has attracted much research interest since many applications have been found in quantum information processing and cryptography (see [1,2,3,5,11,15,17,18,34,38,37] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of perfect state transfer (PST) in quantum communication networks was originally introduced by Bose in [14]. This work has attracted much research interest since many applications have been found in quantum information processing and cryptography (see [1,2,3,5,11,15,17,18,34,38,37] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…These partitions may arise from other graph structures, such as orientable embeddings [25]. The spectral decomposition of a tworeflection walk has been studied [20], and used to find perfect state transfer in circulant graphs [24].…”
Section: Two-reflections Modelmentioning
confidence: 99%
“…We refer [3,21] for example. Although not as numerous as in continuous-time quantum walks, we can find studies of perfect state transfer also in discrete-time quantum walks [2,16,17,19,23,24,26,27,28]. These studies are briefly summarized in Section 1 of [27].…”
Section: Introductionmentioning
confidence: 99%
“…Although not as numerous as in continuous-time quantum walks, we can find studies of perfect state transfer also in discrete-time quantum walks [2,16,17,19,23,24,26,27,28]. These studies are briefly summarized in Section 1 of [27]. Recently, state transfer in discrete-time quantum walks has been studied also from the viewpoint of algebraic graph theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation